2010
DOI: 10.1371/journal.pone.0010036
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Epidemic Monitoring and Forecasting of H1N1-2009 Using Influenza-Like Illness from General Practice and Family Doctor Clinics in Singapore

Abstract: BackgroundReporting of influenza-like illness (ILI) from general practice/family doctor (GPFD) clinics is an accurate indicator of real-time epidemic activity and requires little effort to set up, making it suitable for developing countries currently experiencing the influenza A (H1N1 -2009) pandemic or preparing for subsequent epidemic waves.Methodology/Principal FindingsWe established a network of GPFDs in Singapore. Participating GPFDs submitted returns via facsimile or e-mail on their work days using a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(157 citation statements)
references
References 46 publications
(47 reference statements)
6
151
0
Order By: Relevance
“…28 Assessing surveillance tools during the early pH1N1 epidemic period in Singapore, investigators concluded that the high levels of "background noise" within acute respiratory illness surveillance data provide poorer resolution of influenza epidemic activity than does influenza-like illness. 30 Just as the number of secondary cases of acute respiratory illness considerably over-represents the true incidence of pH1N1 infection among passengers, it is also likely that some asymptomatic or mildly symptomatic passengers with pH1N1 infection, or those with atypical symptoms such as diarrhea, were not identified. From our investigation of travel contacts, serologic testing identified 3 individuals with evidence of asymptomatic pH1N1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…28 Assessing surveillance tools during the early pH1N1 epidemic period in Singapore, investigators concluded that the high levels of "background noise" within acute respiratory illness surveillance data provide poorer resolution of influenza epidemic activity than does influenza-like illness. 30 Just as the number of secondary cases of acute respiratory illness considerably over-represents the true incidence of pH1N1 infection among passengers, it is also likely that some asymptomatic or mildly symptomatic passengers with pH1N1 infection, or those with atypical symptoms such as diarrhea, were not identified. From our investigation of travel contacts, serologic testing identified 3 individuals with evidence of asymptomatic pH1N1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used a single data source [1,19,20] or a primary data source that was modulated by a secondary data source ('ILI+') [21,22]; in both cases single datasets were used to generate and evaluate the forecasts.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…A variety of recursive Bayesian estimation methods (‘filters’) have been used for such forecasting purposes,1, 2 often in combination with Internet search query surveillance data and mechanistic models of infection 3, 4, 5, 6, 7, 8…”
Section: Introductionmentioning
confidence: 99%